Yield and quality evaluation of ginger (Zingiber officinale Rosc) genotypes under high rainfall zone of Tamil Nadu - Balakumbahan, R; Joshua, J P (Journal of Spices and Aromatic Crops, 2017)
An experiment on ginger was undertaken between April 2012 to March 2015 at Horticultural Research Station, Pechiparai with an objective to identify suitable ginger cultivar or accession with higher yield and quality attributes suitable for high rainfall zone of Tamil Nadu. Twenty four ginger genotypes, local strains and varieties were collected from different ginger growing tracts of India and evaluated for their performance in high rainfall region. Among the twenty four genotypes tested, the accession Z. O- 4 recorded higher fresh rhizome yield (22.16 ha-1) than other genotypes whereas Z. O - 6 recorded highest dry recovery per cent (22.47%). Higher oleoresin and fibre content was recorded in genotypes Z. O – 5 (9.56%) and Z . O – 17 (11.20%) respectively.